An Analysis of the Political Parties Evolution in the Parliamentary Elections in Romania - Andi MIHALACHE; Ecaterina Cornelia UNGUREANU; Liliana Mihaela MOGA (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
An important component of the system created in a democratic society for fulfilling specific activities through the institutions and bodies belonging to the administrative apparatus of the state is the political formations. A fundamental element of democracy is the existence of political formations and pluripartyism. This research analyses the evolution of the parliamentary elections held in Romania from 1992 to 2020, including the evolution of the specific legal framework. The results reveal the fact that one party, individually or in different alliances, was present at all electoral consultations regarding the election of the legislature. Moreover, the human resource mobility is representative of political organizations by generating a continuous flow of members and can become a phenomenon who can conduct to changes the party's management, and the political programs.